TOURISM DEVELOPMENT POTENTIAL OF COASTAL ISLAND SYSTEM IN VIETNAM - Khanh, Uong Dinh (Vietnam Journal of Marine Science and Technology, 2016)
Coastal island system in Vietnam distributes and stretches over 2000 km from Quang Ninh coastal sea to Kien Giang coastal sea. Because of the distribution in tropical monsoon belt, coastal island system ownes tremendous values of natural tourism potential; which are maritime climate with mild sunshine, and the place that contains a diversity of terrain, landscape and sea-island biological resources. In the coastal islands, there also exist various types of humanistic tourism resources, including ancient architectures, historical, cultural and archaeological relics, folk festivals and regional food culture. The values of natural and humanistic tourism potential of coastal islands are the foundation for the development of unique sea-island tourism, and the establishment of national and international famous tourism centers. The islands having potential and advantages for tourism development are firstly Vinh Thuc island, Van Don island area, Co To - Thanh Lam island group, islands in Ha Long - Bai Tu Long bay (Quang Ninh), Cat Ba (Hai Phong), Cu Lao Cham (Quang Nam), Ly Son (Quang Ngai), Hon Tre (Khanh Hoa), Phu Quy (Binh Thuan), Con Dao (Ba Ria-Vung Tau) and Phu Quoc (Kien Giang).